Enhanced Photocatalytic H2 Generation by Light-Induced Carbon Modification of TiO2 Nanotubes - Nasir, Amara; Tesler, Alexander; Mohajernia, Shiva; Qin, Shanshan; Schmuki, Patrik; Mazare, Anca Valentina; Yasin, Tariq (ChemistryOpen, 2023)
Titanium dioxide (TiO2) is the material of choice for photocatalytic and electrochemical applications owing to its outstanding physicochemical properties. However, its wide bandgap and relatively low conductivity limit its practical application. Modifying TiO2 with carbon species is a promising route to overcome these intrinsic complexities. In this work, we propose a facile method to modify TiO2 nanotubes (NTs) based on the remnant organic electrolyte retained inside the nanotubes after the anodization process, that is, without removing it by immersion in ethanol. Carbon-modified TiO2 NTs (C-TiO2 NTs) showed enhanced H2 evolution in photocatalysis under UV illumination in aqueous solutions. When the C-TiO2 NTs were subjected to UV light illumination, the carbon underwent modification, resulting in higher measured photocurrents in the tube layers. After UV illumination, the IPCE of the C-TiO2 NTs was 4.4-fold higher than that of the carbon-free TiO2 NTs.
CRIS-Team Scopus Importer:2023-12-22
Keywords: annealing; hydrogen evolution; organic electrolytes; photoelectrochemical water splitting; TiO